Polemics of the Islamic caliphate: A view from Ali Abd. Al-Raziq - Fadzli, Adam; Rahimah, Embong; Abdul Hakim, Abdullah (Mediterranean Centre of Social and Educational Research, 2015)
While many Muslim sects are in agreement of the necessity of the Islamic Caliphate or Khilafah, modelled upon the ideal caliphate of the Prophet and the four rightly-guided caliphs, its necessity is sometimes completely denied. A very controversial view is that advanced by the Egyptian, Ali Abd. al-Raziq (1888-1966) in his treatise al-Islam wa Usul al-Hukm (Islam and the Principles of Government) published in 1925. This paper reviews the argument forwarded by Ali Abd. al-Raziq on the necessity of the Islamic Caliphate using a secondary data analysis and published materials written by scholars on this issue. It is found that the nature and some fundamental principles of the khilafah arose very early in Islam and has continued to provoke discussion into the modern world. Amongst Ali Abd. al-Raziq’s views were the claim that caliphate has no basis, whether in the Qur’an, the traditions or the consensus (ijmac) and the assertion of separation between religion and political power. His view, which remarks violent controversy in the modern Muslim world, is discussed throughout this paper.